Relationship between pain, stiffness and function of knee osteoarthritis with occupational physical activity - Dey, Protyay; Sultan, Mohammad Imtiaz; Arif, M. Saiful; Islam, Mohammed Taherul; Deb, Aparna; Barua, Anupam; Ullah, Enshad Ekram; Hassan, Muhammad Habib; Dee, Deepannita; Tasnim, Sanjida (International Journal of Research in Medical Sciences, 2026)
Background: Osteoarthritis (OA) is a multifactorial disease with strong genetic and occupational components. Although published studies have described several risk factors for OA, very few studies have investigated the contribution of occupational physical activity in debilitating pain, stiffness and physical function of knee OA patients. Methods: This is a hospital based cross-sectional observational study and was carried out in the Medicine department of Chittagong Medical College Hospital (CMCH). Total 200 patients with knee OA were approached for inclusion. Subjects were selected by appropriate inclusion criteria. A thorough history of every case and face to face interview was taken by a predesigned questionnaire after getting the written informed consent of the patient. Results: Among 200 subjects, majority were in age group 51-70 years (86%). Male female ratio was 1:1. Mean duration of exposure of standing, walking, seating, squatting, lifting weight, climbing and kneeling was 27.88±8.105 years, 26.59±9.37 years, 30.63±7.36 years, 27.21±7.95 years, 23.18±9.35 years, 27.42±9.93 years, 35.4±.52 years accordingly and Mean doses of exposure was 3.41±2.71 hours/day, 2.55±5.21 miles/day, 3.13±2.46 hours/day, 1.34±1.53 hours/day, 2.70±6.42 kg/day, 73.66±16.64 flights/day, 2.57±1.33 hours/day. Mean pain, stiffness and physical function score was 13.05 (±3.59), 2.58 (±2.68) and 59.66 (±6.96). Of all, 70% had moderate Western Ontario and McMaster university osteoarthritis index (WOMAC) score, 26% had severe and 4% had low score. Conclusions: Significant association was found between Severity of WOMAC score and duration and dose of exposure to occupational physical activity in their life. However, further study with appropriate design is recommended before drawing a final conclusion.